PENGARUH KUALITAS PELAYANAN DAN PREMI TERHADAP KEPUASAN PESERTA DI BPJS KESEHATAN KANTOR CABANG SIBOLGA - Elisabet Tambunan; Mery Lani Purba; Tohonan Silalahi; Maria Hutagalung (JURNAL MUTIARA MANAJEMEN, 2025)
This research aims to ascertain how participant satisfaction at the BPJS (Social Security Administration) Health Office, Sibolga Branch, is impacted by service quality and premiums. Partially and concurrently, the impacts of premiums and service quality on participant satisfaction are examined. Quantitative research is the research methodology employed. Through a survey method, questionnaires were given directly to BPJS Health participants at the Sibolga Branch in order to collect data. 99 BPJS Health employees from the Sibolga Branch make up the study's sample. The analysis methods employed include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that: (1) the service quality variable has a positive and significant effect on participant satisfaction, with a value of 9.113; (2) the premium variable has a positive and significant effect on participant satisfaction, with a value of 3.629; (3) the service quality and premium variables simultaneously have a positive and significant effect, with a value of 68.931; (4) based on the coefficient of determination (R²), the value is 0.590 or 59%, while the remaining 41% is influenced by other variables not examined in this study, such as location, promotion, and others.